Reforming the implementation of European structural funds: A next development step - Jochen Lang; Frieder Naschold; Bernd Reissert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
The authors assess the performance of the Structural Funds' implementation system in six Member States of the European Union. Considering the strengths and weaknesses, they develop a reform model for the implementation of European structural policy after 1999. The strengths of the existing implementation system lie mainly in innovation effects triggered by the Structural Funds' model of policy implementation. Its main weaknesses, inter alia, are an interwoven structure of the decision-making processes, an insufficient time management and a lack of in-built improvement loops in the implementation process. To overcome these shortcomings, the authors propose a strategic management and decentralisation model. It demands a de-coupling of strategic programming on the one hand, and detailed programming and implementation on the other. Under this model, the Commission and the Member State would negotiate on the strategic issues. In the framework of the agreement, the Member State together with the monitoring committees would be responsible for the implementation of the programmes. Strengthened feedback loops would help to assure the attainment of the strategic objectives. – – Die Autoren untersuchen die Leistungsfähigkeit des Implementationssystems der Strukturfondsförderung in sechs Mitgliedstaaten der Europäischen Union. Vor dem Hintergrund der Stärken und Schwächen entwickeln sie ein Reformmodell zur Implementation der Strukturfonds in der nächsten Förderperiode nach der Reform 1999. Die Stärken des bestehenden Implementationssystems liegen vor allem in den prozeduralen Innovationen, die z.T. auf das Politikmodell der Strukturfonds und seine Kopplung an mitgliedstaatliche Verwaltungsprozesse zurückgeführt werden können. Die wichtigsten Schwächen sind u.a. die verflochtene Struktur der Entscheidungsprozesse, ein ungenügendes Zeitmanagement und fehlende inhärente Verbesserungsmechanismen des Implementationsprozesses. Um diese Schwächen zu überwinden, schlagen die Autoren ein strategisches Management- und Dezentralisierungsmodell vor. Sein Kern besteht in der Trennung von strategischer Programmierung einerseits und Detailprogrammierung und Implementation andererseits. Die Europäische Kommission und der jeweilige Mitgliedstaat handeln demnach die strategischen Teile der Programme aus. Im Rahmen dieser strategischen Vereinbarung ist dann der Mitgliedstaat für die Detailprogrammierung und Umsetzung der Programme verantwortlich, wobei er vom Begleitausschuß unterstützt wird. Verstärkte Feedbackinstrumente tragen dazu bei, die Einhaltung der strategischen Vorgaben zu sichern.
Keywords: 300; EU-Strukturfonds; Einführung; Verwaltungsreform; EU-Staaten